2019
DOI: 10.1186/s13287-019-1374-y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and partial inhibition of GLI1 in neural stem cells (NSCs) results in the early maturation of NSC derived oligodendrocytes in vitro

Abstract: Background: Oligodendrocytes are a type of glial cells that synthesize the myelin sheath around the axons and are critical for the nerve conduction in the CNS. Oligodendrocyte death and defects are the leading causes of several myelin disorders such as multiple sclerosis, progressive multifocal leukoencephalopathy, periventricular leukomalacia, and several leukodystrophies. Temporal activation of the Sonic Hedgehog (SHH) pathway is critical for the generation of oligodendrocyte progenitors, and their different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Previous studies have demonstrated that autologous and allogeneic AD-MSCs can be useful in the treatment of various diseases such as MS, diabetes, Parkinson's disease, autoimmune encephalomyelitis (56)(57)(58)(59). In line with this notion, Li et al revealed that intravenously injection of AD-MSC to EAE mice contributed to the reduction in infiltrations of inflammatory cells in the CNS and significantly inhibited demyelination and axonal loss (8,59). These cells release various growth factors including anti-apoptotic, angiogenic and neurotrophic mediators which have significant roles in many cellular mechanisms such as cell differentiation, proliferation, and maturation (60).…”
Section: Human Adipose-derived Mscs (Ad-mscs)mentioning
confidence: 91%
“…Previous studies have demonstrated that autologous and allogeneic AD-MSCs can be useful in the treatment of various diseases such as MS, diabetes, Parkinson's disease, autoimmune encephalomyelitis (56)(57)(58)(59). In line with this notion, Li et al revealed that intravenously injection of AD-MSC to EAE mice contributed to the reduction in infiltrations of inflammatory cells in the CNS and significantly inhibited demyelination and axonal loss (8,59). These cells release various growth factors including anti-apoptotic, angiogenic and neurotrophic mediators which have significant roles in many cellular mechanisms such as cell differentiation, proliferation, and maturation (60).…”
Section: Human Adipose-derived Mscs (Ad-mscs)mentioning
confidence: 91%
“…One NSC subset, which is enriched in the ventral SVZ, expresses the transcription factor Gli1 and generates interneurons in the olfactory bulb and astrocytes in the healthy mouse brain 26,27 . This population of NSCs is also present in the human SVZ 27 as well as in NSCs derived from human induced pluripotent stem cells and human embryonic stem cells 28 . Remarkably, and in contrast to its fate in the healthy adult brain, this Gli1 pool of NSCs is specifically recruited to the white matter in response to demyelination and go on to differentiate into remyelinating oligodendrocytes 20,27,29 .…”
Section: Background and Summarymentioning
confidence: 93%
“…Remarkably, and in contrast to its fate in the healthy adult brain, this Gli1 pool of NSCs is specifically recruited to the white matter in response to demyelination and go on to differentiate into remyelinating oligodendrocytes 20,27,29 . Inhibition of Gli1 in these cells further enhances their remyelination potential and is neuroprotective resulting in functional improvement in mouse models of MS 27,28 . Importantly, Gli1 expressing stem-like cells respond to injury in other organs like the liver, lung, bone marrow, kidney and heart with loss of Gli1 resulting in attenuated injury in these organs [30][31][32][33][34][35][36][37] .…”
Section: Background and Summarymentioning
confidence: 99%
“…In vivo , blocking SHH may lead to insufficient differentiation of granular neurons and Bergmann glial cells and abnormal development of Purkinje neurons ( Wang and Almazan, 2016 ). According to numerous research studies, SHH can mediate to produce oligodendrocyte precursors ( Namchaiw et al, 2019 ; Starikov and Kottmann, 2020 ). By the chemical inhibitor or anti-SHH antibody, inhibiting SHH may inhibit the differentiation of oligodendrocytes ( Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%